1988
DOI: 10.1530/jrf.0.0820799
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of genetic differences in hormone-induced ovulation rate in mice

Abstract: Summary. Major genetic differences in hormone-induced ovulation rate were not explained by strain differences in age at puberty, by maturation and ovulation of follicles by endogenous gonadotrophins, or by differential responses to gonadotrophins at different ages. The major genetic differences in hormone-induced ovulation rate were explained by strain differences in ovarian responsiveness to exogenous gonadotrophins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

1988
1988
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 14 publications
1
18
0
Order By: Relevance
“…These results contrast with the findings of Eleftheriou et al (1972), Eleftheriou & Kristal (1974), and Spearow (1980) of large strain differences in ovulation rate induced by a single injection of gonadotrophin. Other studies suggest that the genetic differences in hormone-induced ovulation rate observed in the present study were due to genetic differences in the ovarian responsiveness to large doses of exogenous gonadotrophins (Spearow, 1988).…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…These results contrast with the findings of Eleftheriou et al (1972), Eleftheriou & Kristal (1974), and Spearow (1980) of large strain differences in ovulation rate induced by a single injection of gonadotrophin. Other studies suggest that the genetic differences in hormone-induced ovulation rate observed in the present study were due to genetic differences in the ovarian responsiveness to large doses of exogenous gonadotrophins (Spearow, 1988).…”
Section: Discussionsupporting
confidence: 52%
“…1 of the present study, or the number of fresh eggs ovulated by 5 i.u. hCG alone (Spearow, 1988), suggests that strain differences in the maturation of follicles by endogenous gonadotrophins, which can be ovulated by 5 i.u. PMSG or 5 i.u.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, this issue has been poorly investigated and more studies are needed (James et al 2006). Little is known also about possible strain differences in the onset and expression of puberty in male mice (Osadchuk et al 2008), although studies carried out in female mice demonstrated different strain-specific profiles of sexual maturation (Spearow 1988). Nonetheless, as the onset of puberty for either strain certainly falls within the agewindow studied here, it is unlikely that strain differences in the onset of puberty account for the lack of age-differences in startle-like behaviors in the D2 strain.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic strain variations in mice with regard to in vitro fertilization (Kaleta 1977), cleavage rates (McLaren & Bowman 1973, Luckett & Mukherkee 1986, pH regulation (Steeves et al 2001), parthenogenetic activation (Gao et al 2004, Ibáñ ez et al 2005) and preimplantation development (Suzuki et al 1996) buttress the well-known relationship between fecundity and genetic background amongst hybrid F1, inbred and outbred lines (Silver 1995). Additionally, variations in hormone sensitivity influence ovulation rate amongst different mouse strains (Spearow 1988, Spearow et al 1999) and the rate of meiotic maturation in vivo or in vitro can vary depending on genetic background (Polanski 1986(Polanski , 1997. Thus, it seems likely that some of the genetic factors that specify embryo quality find their roots in maternal preconceptional processes associated with oogenesis and ovulation.…”
Section: Introductionmentioning
confidence: 99%